Role of E-Commerce on Entrepreneurial Welfare in Indonesia - Fitriani Aditya Putri (Politeknik Statistika STIS, 2023)
This study aims to determine the role of the use of e-commerce on the welfare of entrepreneurs in Indonesia during the Covid-19 pandemic. Based on the August 2021 Sakernas data sourced from BPS, the estimation results using binomial logistic regression show that e-commerce has an important role in increasing the welfare of entrepreneurs in Indonesia during the Covid-19 pandemic. The use of e-commerce was able to increase the income of entrepreneurs in Indonesia. Entrepreneurial activities using e-commerce are quite promising in the midst of limited business fields and post-pandemic economic recovery conditions in Indonesia, so the government needs to provide economic support and training to develop digital entrepreneurship activities in the labor force in Indonesia.